The Role of Wijaya Kusuma's Youth Information and Counseling Center (PIK-R) on Adolescent Health Problems - Khoiriyah Isni; Ratu Matahari (International Journal of Public Health Science (IJPHS), 2018)
The issue of adolescent health is important for national development. Adolescents need a place that can provide facilities in the form of correct information and life skills improvement programs. So as to deal with various health problems of adolescent. Government efforts to overcome these problems through the establishment of the Youth Information and Counseling Center (PIK-R) that can be done in schools. PIK-R in schools that have been formed can be assessed its role to adolescent health problems. The purpose of this research is to know the role of PIK-R Wijaya Kusuma in overcoming the health problem of adolescent among non-members of PIK-R. The research used qualitative design with case study approach. The data were collected by focus group discussion (FGD) technique on 10 non PIK-R member students. The results of the study reported that PIK-R Wijaya Kusuma has an important role as health information source for non PIK-R member students in facing adolescent health problems. Besides, teachers and NGOs. Awareness of non-members of PIK-R Wijaya Kusuma related to adolescent's vulnerability to high adolescent health problems, peers and family plays an important role in adolescent health behavior.